Validation of Induced Microglia-Like Cells (iMG Cells) for Future Studies of Brain Diseases - Banerjee, Atoshi; Lu, Yimei; Do, Kenny; Mize, Travis; Wu, Xiaogang; Chen, Xiangning; Chen, Jingchun (Frontiers in Cellular Neuroscience, 2021)
Microglia are the primary resident immune cells of the central nervous system that maintain physiological homeostasis in the brain and contribute to the pathogenesis of many psychiatric disorders and neurodegenerative diseases. Due to the lack of appropriate human cellular models, it is difficult to study the basic pathophysiological processes linking microglia to brain diseases. In this study, we adopted a microglia-like cell model derived from peripheral blood monocytes with granulocyte-macrophage colony-stimulating factor (GM-CSF) and interleukin-34 (IL-34). We characterized and validated this in vitro cellular model by morphology, immunocytochemistry, gene expression profiles, and functional study. Our results indicated that the iMG cells developed typical microglial ramified morphology, expressed microglial specific surface markers (P2YR12 and TMEM119), and possessed phagocytic activity. Principal component analyses and multi-dimension scaling analyses of RNA-seq data showed that iMG cells were distinct from monocytes and induced macrophages (iMacs) and clustered closer to human microglia and hiPSC-induced microglia. With cluster analyses, we found that iMG cells, but not monocytes, were closely clustered with human primary microglia. Further pathway and relative expression analysis indicated that unique genes from iMG cells were involved in the regulation of the complement system, especially in the synapse and ion transport. Overall, our data demonstrated that the iMG model mimicked many features of the brain resident microglia, highlighting its utility in the study of microglia function in many neurological disorders, such as schizophrenia and Alzheimer’s disease (AD).